Implementation of Family Involvement Based On Mark 2: 1-12 In Circles Families of Patients Treated at Yaspis Lubuk Pakam - Bernard Lubis (ADI Publisher, 2020)
The purpose of this study was to determine the tendency of the description of the implementation of family involvement based on Mark 2: 1-12 among the families of patients treated at YASPIS Lubuk Pakam; to find out which indicators are dominantly implemented from indicators of family involvement based on Mark 2: 1-12 among the families of patients treated at YASPIS Lubuk Pakam; and also to find out which background categories are dominant in influencing the implementation of family involvement based on Mark 2: 1-12 among the families of patients treated by YASPIS Lubuk Pakam. With a theoretical basis from Mark 2: 1-12. From these texts the following dimensions and indicators were obtained: concerning family involvement. There are 2 dimensions: believe Jesus has the power to heal and act with faith. The first dimension has two indicators, namely: know Jesus has the power to heal, and believe that Jesus has the power to Heal and the second dimension, has two indicators: bring the sick family to the place where Jesus is, and fight until the sick family is healed. And the family background category of patients treated at YASPIS Lubuk Pakam. And the results of the research discussion obtained the results that the first hypothesis that reads: implementation of family involvement based on Mark 2: 1-12 among the families of patients treated at YASPIS Lubuk Pakam is being proven ill. The second hypothesis, which reads: a dominant indicator is implemented from indicators challenging family involvement based on Mark 2: 1-12 among the families of patients treated at YASPIS Lubuk Pakam is knowing that Jesus has the power to heal is not proven. The dominant indicator implemented is believing that Jesus has the power to heal. And the third hypothesis, which reads: the dominant background category in influencing the implementation of family involvement based on Mark 2: 1-12 among the families of patients treated at YASPIS Lubuk Pakam is the category of spiritual activity is proven. With the results of this study it is hoped that the families of patients treated at YASPIS Lubuk Pakam need to pay attention to the results of this study and the implications and suggestions contained in this thesis, if they want their families who are sick to be treated quickly to heal.